Peranan BUMDesa dalam Meningkatkan Kemandirian Ekonomi Desa - Gayatri, Gayatri; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi; Vol 30 No 6 (2020)DO - 10.24843/EJA.2020.v30.i06.p19, 2020)
BUMDesa is an elaboration of the vision of national development that is the realization of a sovereign, independent, and personality based on mutual cooperation. In the Province of Bali only 65% ??of the villages have BUMDesa. BUMDesa is expected to be a driving force for the village economy. The purpose of this study is to determine the role of BUMDesa in increasing the economic independence of the village. The population in this study are all village-owned enterprises in the Province of Bali. The location of the study was conducted in Gianyar Regency. The sample collection technique uses purposive sampling. Data collection techniques are carried out through questionnaires. Data analysis techniques using multiple linear regression. This research proves that partially, economic independence has a positive role in BUMDesa in Gianyar Regency. Intellectual independence has a positive role in BUMDesa in Gianyar Regency. And organizational independence has a positive role in BUMDesa in Gianyar Regency. Together economic independence, intellectual independence and organizational independence have a positive role in BUMDesa in Gianyar Regency. Keywords: BUMDesa ; Economic Independence.